Perceptions And Preferences of Indonesian Muslim Tourists for Halal Tourism Facilities and Conditions in Sembalun - Iswanto, Dedy; S. Sangadji, Suwandi; Nazwin, Asfarony Hendra (KAMBOTI: Jurnal Sosial dan Humaniora, 2023)
The purpose of this study was to determine the perceptions and preferences of Indonesian muslim tourists for halal tourism facilities and conditions in Sembalun. To meet the proving result, this research used descriptive research methods. The samples of this research were domestic Muslim tourists who have visited Sembalun. The analytical tool used in this study is Descriptive Statistical Analysis. The results of this study indicate that the government's efforts in promoting halal tourism have not been fully successful, because only a small proportion of respondents consider Sembalun as a halal tourist destination. the tourists emphasized that toilets and places of worship are important facilities that must exist in Sembalun.